A review of pooled‐sample strategy: Does complexity lead to better performance?. Issue 4 (13th May 2022) - Song, Yu; Wang, XueLiang; Xiao, YanQun; Wang, Hualiang
Abstract: The outbreak of coronavirus disease 2019 (COVID‐19, caused by SARS‐Cov‐2) is a big challenge for global health systems and the economy. Rapid and accurate tests are crucial at early stages of this pandemic. Reverse transcription‐quantitative real‐time polymerase chain reaction is the current gold standard method for detection of SARS‐Cov‐2. It is impractical and costly to test individuals in large‐scale population screens, especially in low‐ and middle‐income countries due to their shortage of nucleic acid testing reagents and skilled staff. Accordingly, sample pooling, such as for blood screening for syphilis, is now widely applied to COVID‐19. In this paper, we survey and review several different pooled‐sample testing strategies, based on their group size, prevalence, testing number, and sensitivity, and we discuss their efficiency in terms of reducing cost and saving time while ensuring sensitivity. Abstract : Fast, efficient, accurate and cost‐saving testing of COVID‐19 is the most challenge for epidemic control. However, it's hard to balance these technical criteria. As survey research, the authors intend to discuss the mostly used testing strategies, trying to figure out which kinds are "optimal" under certain circumstances.